Menigkatkan Kemampuan Kognitif Mengenal Bentuk Geometri Melalui Media Bahan Alam Batu Pelangi - Winda Widyaningtyas; Destita Shari; Nanang Rokhman Saleh; Berda Asmara (UIN Sultan Maulana Hasanuddin Banten, 2021)
Cognitive development is the basis for a child's ability to think such as skills and understand what happens in his environment. This study aims to improve cognitive abilities in recognizing geometric shapes through the natural material media of rainbow stones in child B at PPT Tunas Bangsa City Surabaya. This Classroom Action Research consists of 2 cycles, each cycle consisting of 4 stages: Planning, Action, Observation, and Reflection. The subjects of this study were 24 children of PPT Tunas Bangsa. Data collection techniques using observation and documentation. The results of the research in the first cycle showed a cognitive development of 55.83% and in the second cycle research showed a cognitive development of 83.3% with the achievement of the criteria for BSB (Very Good Development). Based on the results of the research that has been done, it can be concluded that the natural material media of rainbow stone can improve cognitive abilities to recognize geometric shapes in children aged 3-4 years at PPT Tunas Bangsa Surabaya. Keywords: Cognitive Development; Rainbow Stone MediaReferencesAqib, Z. (2019). Penelitian tindakan kelas. Bandung: Yrama Widya. Arikunto, S. (2010). Prosedur Penelitian Suatu Pendekatan Praktik, Jakarta: Rineka Cipta..(2013). Prosedur Penelitian Suatu Pendekatan Praktek. Edisi Revisi VI. Jakarta: Rineka Cipta. Fauziah, N. (2013). Penggunaan Media Bahan Alam Untuk Meningkatkan Kreativitas Anak. Jurnal Ilmiah Visi, 8(1), 23–30. Hidayat, W. D. (2018). Kompetensi Pedagogik Guru Dalam Menggunakan Media Pembelajaran Di Madrasah Ibtidaiyah (Studi Kasus Di MIN Jejeran). Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 8(1), 35–48. Hrp, T. N. (2018). PENGARUH KEGIATAN BERMAIN KONSTRUKTIF TERHADAP KEMAMPUAN MENGENAL BENTUK GEOMETRI PADA ANAK KELOMPOK B DI RA SABILA AMANDA. JURNAL RAUDHAH, 6(2). Imroatun, I., Widat, F., Fauziddin, M., Farida, S., Maryam, S., & Zulaiha. (2021). Youtube as a Media for Strengthining Character Education in Early Childhood. Journal of Physics: Conference Series, 1779(1), 012064. https://doi.org/10.1088/1742-6596/1779/1/012064Ismail, J., & Budian, A. R. S. (2019). PENINGKATAN HASIL BELAJAR PADA MATA PELAJARAN BAHASA INDONESIA MATERI MENGARANG DENGAN METODE CRITICAL INCIDENT SISWA KELAS VA SD NEGERI UNGGULAN 1 PULAU MOROTAI. e-Jurnal Mitra Pendidikan, 3(10), 1314–1330. Juhji, J. (2016). Pembelajaran Sains Pada Anak Raudhatul Athfal. As-Sibyan : Jurnal Pendidikan Anak Usia Dini, 1(1), 49–59. Khadijah, K. (2016). Pengembangan kognitif anak usia dini. Perdana Publishing. Menteri Pendidikan dan Kebudayaan Republik Indonesia. (2014). Standar Nasional Pendidikan Anak Usia Dini. Peraturan Menteri Pendidikan Dan Kebudayaan Republik Indonesia, 13. Muqdamien, B., Umayah, U., Juhri, J., & Raraswaty, D. P. (2021). Tahap Definisi Dalam Four-D Model Pada Penelitian Research & Development (R&D) Alat Peraga Edukasi Ular Tangga Untuk Meningkatkan Pengetahuan Sains Dan Matematika Anak Usia 5-6 Tahun. Intersections, 6(1), 23–33. https://doi.org/10.47200/intersections.v6i1.589Nuangchalerm, P., Prachagool, V., Prommaboon, T., Juhji, J., Imroatun, I., & Khaeroni, K. (2020). Views of primary thai teachers toward STREAM education. International Journal of Evaluation and Research in Education, 9(4), 987–992. https://doi.org/10.11591/ijere.v9i4.20595Nuryati, N. (2017). Perkembangan intelektual pada anak usia dini. aṣ-ṣibyān: Jurnal Pendidikan Anak Usia Dini, 2(2), 59–78. Prihantoro, A., & Hidayat, F. (2019). Melakukan Penelitian Tindakan Kelas. Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 9(1), 49–60. Setyowati, E., Hidayati, I. S., & Hermawan, T. (2020). Pengaruh Penggunaan Multimedia Interaktif Terhadap Pemahaman Konsep Dalam Pembelajaran Matematika Di MTs Darul Ulum Muhammadiyah Galur. Intersections, 5(2), 26–37. https://doi.org/10.47200/intersections.v5i2.553Susanto, A. (2011). perkembangan anak usia dini :pengantar dalam berbagai aspeknya (pertama). kencana prenadamedia group. Susanto, A. (2018). Pendidikan Anak Usia Dini (Konsep dan Teori). Jakarta: Bumi Aksara, 87. Trianto, M. P. (2010). Mendesain Model Pembelajaran Inovatif-Progresif: Konsep, Landasan dan Implementasinya pada kurikulum Tingkat Satuan Pendidikan (KTSP). Jakarta: Kencana. Umayah, U., Juhri, J., Muqdamien, B., Fauzia, W., & Maulida Qolbiyah, S. M. (2021). PENGGUNAAN BALOK CUISENIARE UNTUK MEDIA PENGENALAN BILANGAN BAGI ANAK USIA DINI. Intersections, 6(1), 34–42. https://doi.org/10.47200/intersections.v6i1.590Weni, R. P. (2018). Peningkatan Kemampuan Mengenal Lambang Bilangan Melalui Metode Proyek Dengan Media Kartu Pintar Siswa TK Pertiwi Banteran Kecamatan Wangon Kabupaten Banyumas. As-Sibyan : Jurnal Pendidikan Anak Usia Dini, 2(2), 147–163. Zaman. (2014). Media dan Sumber Belajar PAUD. Universitas Terbuka.